Introduction to guoxue : traditional Chinese thoughts, culture, and learning - Zhang, Taiyan, 1869-1936; Cao, Juren, 1900-1972; Wang, Feng, 1976- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book is a collection of Zhang Taiyan's lectures on traditional Chinese thoughts, culture, and learning. Zhang Taiyan is known for his role as an active proponent of Guoxue (Chinese learning) in modern China. This title comprises the transcripts of a series of his lectures on Guoxue given in Shanghai between April and June 1922, and serves as an insightful and influential companion to Guoxue. It systematically introduces the research methods of Guoxue and the development and schools of Chinese classical studies, Chinese philosophy, and Chinese literature, and provides a brilliant analysis of representative figures and works from various periods. It also touches on a wide range of topics in Chinese history, philology, paleography, bibliology, and geography. This book provides Guoxue with many new and thought-provoking ideas and plays a crucial role in the dissemination of Guoxue throughout the world. The title will be essential reading for students and scholars of Sinology and Chinese Studies, as well as the general public interested in traditional Chinese culture"--
Keywords: Chinese philology -- Study and teaching; China -- Study and teaching; FOREIGN LANGUAGE STUDY / Chinese; HISTORY / Asia / China